2008
DOI: 10.1179/174328107x174762
|View full text |Cite
|
Sign up to set email alerts
|

Maximisation of non-coking coals in coke production from non-recovery coke ovens

Abstract: The blast furnace has been, and is likely to remain, the dominant technology for ironmaking. Coke is fed to blast furnace as a fuel and its quality plays a significant role in controlling the performance of the furnace. The quality of coke depends on the quality of coal or its blend, coking parameters and precarbonisation techniques, if any. With decreasing availability and increasing cost of good quality hard coking coal, coke makers face a tough challenge for production of metallurgical coke at competitive r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 3 publications
1
14
0
Order By: Relevance
“…The d 50 of the Waterberg sscc materials varied between 0.6 mm and 1 mm, whereas the crushing fineness was more than 99% < 3.25 mm. The particle sizes of the coals utilized in this study were similar to those suggested for compaction or stamping by various workers in the field, namely 85% to 99% < 3.25 mm (Dash et al, 2005;Kumar et al, 2008, Tiwari et al, 2012Madias and de Córdova, 2013;Rejdak and Wasielewski, 2015). In the case of the Oaky North sample, the d 50 was 0.7 mm with a crushing fineness of 95% < 3.25 mm.…”
Section: Particle Size Distributionsupporting
confidence: 81%
See 1 more Smart Citation
“…The d 50 of the Waterberg sscc materials varied between 0.6 mm and 1 mm, whereas the crushing fineness was more than 99% < 3.25 mm. The particle sizes of the coals utilized in this study were similar to those suggested for compaction or stamping by various workers in the field, namely 85% to 99% < 3.25 mm (Dash et al, 2005;Kumar et al, 2008, Tiwari et al, 2012Madias and de Córdova, 2013;Rejdak and Wasielewski, 2015). In the case of the Oaky North sample, the d 50 was 0.7 mm with a crushing fineness of 95% < 3.25 mm.…”
Section: Particle Size Distributionsupporting
confidence: 81%
“…A less porous coke product, which is beneficial for mechanical strength (Nishioka and Yoshida, 1983). The decrease in total porosity is indicative of limited swelling, restraining pore enlargement and this, presumably, is attributable to the compact nature of the coal bed under high oven bulk density (Nyathi et al, 2013) Closer proximity of coal particles during softening, which results in the development of a stronger bond between the coke cells (Kumar et al, 2008) The induction of homogeneity throughout the coal cake (Kuyumcu, Rosenkranz, and Abel, 2010) An increase in the proportion of less-reactive carbon forms, and an improved degree of crystallization (Nyathi et al, 2013) Decreased porosity causing an increase in the water saturation index, i.e. filling of the total pore volume (Rejdak and Wasielewski, 2015) Improvement in the coke strength owing to increased coal particle contact and increased coke density (Rejdak and Wasielewski, 2015).…”
Section: The Benefits Of An Increase In Coal Cake Bulk Density Includementioning
confidence: 99%
“…8 The analysis of coals used for the study is given in Table 1. Coals A, B are hard coking coals, coals C, D are semi soft and coal E is non-coking coal.…”
Section: Methodsmentioning
confidence: 99%
“…Several models (Bukharkina et al 2012;Dash et al 2005Dash et al , 2012Kishore et al 2011;McKenzie et al 1998;Suresh et al 2012) consider an aggregate of a portion of the vitrinite distribution as an input parameter, in effect creating a weighted R v,max . Kumar et al (2008) reported that the vitrinite reflectance in the range V 9 -V 13 , a commonly used aggregate value, is an improved predictor of the measured Coke Strength after Reaction (CSR) than the mean maximum vitrinite reflectance. The standard deviation or petrographic non-uniformity of the distribution is another attribute used within models, that relates to V-groups and blending decisions (Bulanov et al 2009;Stankevich and Bazegskiy 2013;Stankevich et al 2008;Stankevich and Zolotukhin 2015).…”
Section: Vitrinite Reflectance and Coal Blending Decisionsmentioning
confidence: 99%